Gas-phase grafting for the multifunctional surface modification of silicon quantum dots. Issue 46 (16th November 2022) - Schwan, Joseph; Wang, Kefu; Tang, Ming Lee; Mangolini, Lorenzo
Abstract : Gas-phase modification of silicon quantum dots enables a precise control of their surface functional groups, in turn enabling high photon upconversion efficiency. Abstract : Photon upconversion in systems incorporating inorganic quantum dots (QDs) is of great interest for applications in solar energy conversion, bioimaging, and photodynamic therapy. Achieving high up-conversion efficiency requires not only high-quality inorganic nanoparticles, but also precise control of their surface functional groups. Gas-phase surface functionalization provides a new pathway towards controlling the surface of small inorganic nanoparticles. In this contribution, we utilize a one-step low-temperature plasma technique for the synthesis and in-flight partial functionalization of silicon QDs with alkyl chains. The partially functionalized surface is then modified further with 9-vinylanthracene via thermal hydrosilylation resulting in the grafting of 9-ethylanthracene (9EA) groups. We have found that the minimum alkyl ligand density necessary for quantum dot solubility also gives the maximum upconversion quantum yield, reaching 17% for silicon QDs with Si-dodecyl chains and an average of 3 9EA molecules per particle.